Coupling of capillary electrophoresis with electrospray ionization multiplexing ion mobility spectrometry. Issue 12 (4th April 2019) - Guo, Jianheng; Li, Guozhu; Zhang, Hanghang; Jia, Xu; Meng, Qingyan; Liu, Wenjie
Abstract: In this work, ion mobility spectrometry (IMS) function as a detector and another dimension of separation was coupled with CE to achieve two‐dimensional separation. To improve the performance of hyphenated CE‐IMS instrument, electrospray ionization correlation ion mobility spectrometry is evaluated and compared with traditional signal averaging data acquisition method using tetraalkylammonium bromide compounds. The effect of various parameters on the separation including sample introduction, sheath fluid of CE and drift gas, data acquisition method of IMS were investigated. The experimental result shows that the optimal conditions are as follows: hydrodynamic sample injection method, the electrophoresis voltage is 10 kilo volts, 5 mmol/L ammonium acetate buffer solution containing 80% acetonitrile as both the background electrolyte and the electrospray ionization sheath fluid, the ESI liquid flow rate is 4.5 μL/min, the drift voltage is 10.5 kilo volts, the drift gas temperature is 383 K and the drift gas flow rate is 300 mL/min. Under the above conditions, the mixture standards of seven tetraalkylammoniums can be completely separated within 10 min both by CE and IMS. The linear range was 5–250 μg/mL, with LOD of 0.152, 0.204, 0.277, 0.382, 0.466, 0.623 and 0.892 μg/mL, respectively. Compared with traditional capillary electrophoresis detection methods, the developed CE‐ESI‐IMS method not only provide two sets of qualitative parameters including electrophoresis migration time and ion drift time, ion mobility spectrometer can also provide an additional dimension of separation and could apply to the detection ultra‐violet transparent compounds or none fluorescent compounds.